2013
DOI: 10.1007/s10384-013-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

A prevalence study of IgG4-related ophthalmic disease in Japan

Abstract: Nearly a quarter of orbital lymphoproliferative disorders in Japan are related to IgG4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…[6,16,17] As previously suggested, sIgG4 elevation was preferentially associated with bilateral forms, and was associated with extra-orbital and systemic manifestations of IgG4-RD. [3] Under treatment, sIgG4 normalized in most evaluable patients (5/6 evaluable patients treated for IgG4-ROD) and correlated with clinical and radiological responses of the disease.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…[6,16,17] As previously suggested, sIgG4 elevation was preferentially associated with bilateral forms, and was associated with extra-orbital and systemic manifestations of IgG4-RD. [3] Under treatment, sIgG4 normalized in most evaluable patients (5/6 evaluable patients treated for IgG4-ROD) and correlated with clinical and radiological responses of the disease.…”
Section: Discussionmentioning
confidence: 86%
“…[6,14,16,17] IgG4-ROD was first identified thanks to the reporting of patients with orbital manifestations concomitant to other IgG4-RD manifestations and to the retrospective search of IgG4-RD pathological characteristics in pathological specimen of inflammatory orbital diseases. The frequency of IgG4-ROD ranges 4% to 34% of IgG4-RD patients according to the largest case series published to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed that conditions previously diagnosed as Mikulicz disease as well as various types of lymphoplasmacytic infiltrative disorders are consistent with a diagnosis of IgG4-related disease [1,2]. After the establishment of comprehensive diagnostic criteria for IgG4-related disease in 2012 [3], the diagnostic criteria for IgG4-related ophthalmic disease (IgG4-ROD) have recently been reported, based on both clinical and histopathologic features of ocular lesions [4].…”
Section: Introductionmentioning
confidence: 83%
“…In Japan, MALT lymphoma is the most frequent primary malignancy of the ocular adnexa region, whereas IgG4-related ophthalmic disease (IgG4-ROD) and reactive lymphoid hyperplasia (RLH) are the most common benign LPDs of the ocular adnexa45. The etiologies of most LPDs of the ocular adnexa have been widely investigated, but several other disorders including IgG4-ROD require further study.…”
mentioning
confidence: 99%